2007
DOI: 10.1897/07-201
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Compounds: Toxic Effects Using Algae, Daphnids and the Salmonella/Microsome Test Taking Methodical Quantitative Aspects into Account

Abstract: Heterocyclic aromatic hydrocarbons containing nitrogen, sulfur, or oxygen (NSO-HET), have been detected in air, soil, sewage sludge, marine environments, and freshwater sediments. Since toxicity data on this class of substances are scarce, the present study focuses on possible implications NSO-HET have for ecotoxicity (algae and daphnids) and mutagenicity (Salmonella/microsome test). A combination of bioassays and chemical-analytical quantification of the test compounds during toxicity assays should aid in det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 0 publications
1
17
2
Order By: Relevance
“…Eisenträger et al [12] found that out of the tested substances (similar to the set tested here) only quinoline, 6-methylquinoline and xanthene caused mutagenic effects in the Ames assay with Salmonella typhimurium, while these effects were only apparent in treatments with metabolic activation, i.e. when supplemented with rat liver S9.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…Eisenträger et al [12] found that out of the tested substances (similar to the set tested here) only quinoline, 6-methylquinoline and xanthene caused mutagenic effects in the Ames assay with Salmonella typhimurium, while these effects were only apparent in treatments with metabolic activation, i.e. when supplemented with rat liver S9.…”
Section: Resultsmentioning
confidence: 64%
“…Carbazole was demonstrated to be clastogenic by Jha et al [48] but was not mutagenic in the Ames assay [49] or carcinogenic in mice [43]. The O-heterocyclic compound benzofuran showed very interesting effects, although being negative in the Ames assay [12], [50]; DNA damage, as measured with the Comet assay, as well as the formation of micronuclei was higher in female specimens, both in vivo in rat kidney and in vitro using primary rat and human kidney cultures [51]. Dibenzofuran, a substance that was previously reported not to be genotoxic in a mammalian system was identified to be potent genotixicant in the fish system [52].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations